Ly antigens: markers of T cell function on mouse spleen cells. - Hirst, J; Beverley, P; Kisielow, P; Hoffmann, M; Oettgen, H (1975)
By the use of Ly antisera and complement it is possible to remove subpopulations of mouse T cells from spleen cell suspension. It is shown that these Ly antisera are specific for the Ly alleles carried by the cells. Helper cells from primed or unprimed mice and cells which respond to Con A express Ly-1 antigen but little or no Ly-2 antigen (Ly-1+ phenotype) whereas cells which respond to PHA express both Ly-1 and Ly-2 antigens (Ly-1+2+ phenotype).